Perceived ease of use, perceived usefulness and attitude of transition students in Petaling Perdana district towards the use of apps Tele-Marz new normal learning style of Malay language - Mokhtar, Marzni Mohamed; Abu Bakar, Azrin Shah; Abu Kashim, Nuur Syafiqah; Fakhrurrazey, Sufi Firdaus; Ghazali, Norliza; Khambari, Mas Nida Md.; Abd Rahman, Fadzilah; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2023)
The Covid-19 pandemic that hit the world including Malaysia has changed the educational landscape in the delivery of learning and facilitation (PdPc) from traditional methods to online. The Malay language subject is a core subject that must be studied by students at the secondary school level, including language skills involving oral skills, reading skills and writing skills as well as two other aspects, namely the aspects of literature and grammar. However, transition students at school are identified as the weakest students in mastering Malay in terms of writing, reading and speaking. Conventional learning methods that use learning aids such as written notes or books are less effective in attracting the attention of transition students during PdPc due to the content of Malay lessons that cannot be matched with audio, visual or mobile audio-visual. Therefore, an application known as Tele-Marz Apps, the New Norm Malay Language Learning Style has been produced to deal with the issue. In general, this study aims to examine the perception of ease of use, perception of usefulness and attitude towards the use of Tele-Marz Apps of the New Malay Norm Learning Style among transitional class students. A total of 70 respondents were selected through a cluster random sampling technique involving students in the transition class of the public high school in Petaling Perdana, Selangor. A cross-sectional survey and a structured questionnaire were used for data collection. Data obtained through a questionnaire shows that the mean score of perceived ease of use is 3.643 with a standard deviation of .722; the mean score of perceived usefulness is 3.491 with a standard deviation of .725, and the mean score of attitude towards using is 3.420 with a standard deviation of .674. The findings of this study give an impression that the students' response is positive towards the three constructs used in the study. In conclusion, the Tele-Marz Application: The New Norm Learning Style of the Malay Language has the potential to be implemented in helping transition students master Malay language skills.